Looking in two ways. Poverty in South Africa and its ecclesiological implications - Le Bruyns, C; Pauw, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
This paper briefly presents the complex nature of poverty in South Africa through two lenses. The first lens will look at the economic data and statistics that are available in order to draw a picture of poverty in South Africa. The second lens will point to how the church ought to look at the problem of poverty. Three aspects of poverty are discussed, namely identifying the poor, poverty and service delivery, and poverty and the labour market. In each case the “economic look” is presented, followed by the “ecclesiological look” to that particular aspect. After looking in these two ways, the conclusion briefly reflects on the ways in which the church may respond to the problem of poverty in South Africa.